Analisis Kualitas Manajemen Terpadu Usaha Mikro Kecil Dan Menengah (Studi Kasus Toko Wery Bakery Di Kota Gunungsitoli) - Lase, Septrianita; Eduar Baene; Eliagus Telaumbanua; Martha Surya Dinata Mendrofa (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2024)
This research aims to analyze the quality of integrated management in micro, small and medium enterprises (MSMEs), by taking a case study at the Wery Bakery Shop in Gunungsitoli City. The research method used is qualitative research with a case study approach. Data was collected through in-depth interviews with shop owners and managers, direct observation, and analysis of documents related to operational and financial management. The analysis results show that the Wery Bakery Shop has a number of advantages in implementing integrated management at the MSME level. Human resource, operational and financial management is well coordinated, creating efficiency in daily business processes. However, research also identifies several challenges faced by MSMEs, such as market expansion and technology integration. These findings provide valuable insights for MSME owners and related parties to improve the quality of integrated management. Strategic recommendations are proposed, including improving managerial skills, applying information technology, and more effective marketing strategies to face ever-evolving market dynamics. It is hoped that this study can make a positive contribution to the development of MSMEs in Gunungsitoli City and the like.